Chapter 2 Practical gender in critical pedagogy Analyzing everyday objects - Harmat, Gal (Taylor & Francis, 2020)
This chapter offers a theoretical and methodological framework for implementing feminist critical pedagogy in compulsory courses in gender studies. The method examined presents a gender analysis of daily objects by students as a means of dealing with resistance to gender studies and feminist theory, as well as creating a consciousness-changing experience for the participants.